Idealized single-forcing GCM simulations with GFDL CM2.1 - Erb, Michael; Broccoli, Anthony; Raney, Bryan (Zenodo, 2018)
This repository contains a set of single-forcing general circulation model (GCM) simulations run with the Geophysical Fluid Dynamics Laboratory (GFDL) Climate Model 2.1 (CM2.1). In each of these equilibrium simulations, one climate forcing was altered while all others were held constant at preindustrial levels, modeling the climate response to individual climate forcings. Simulations were run for obliquity (low and high obliquity), precession (four phases of the precession cycle with high eccentricity, and one simulation with eccentricity set to zero), half CO 2 , and LGM-sized ice sheets. The values chosen for the orbital simulations represent the extreme values of the past 900 thousand years. Simulations were run for at least 500 years, and forcings do not change from year to year. The uploaded files are 100 year annual-means and monthly climatologies. Variables are presented for the atmosphere, ocean, sea ice, and land. Monthly ocean files are not currently available; please contact Michael Erb at michael.p.erb@gmail.com if you are interested in those results. === FORCINGS === Preindustrial climate forcings were set to the following values: - Obliquity: 23.439° - Longitude of perihelion: 102.93° - Eccentricity: 0.0167 - CO 2 : 286 ppm - Ice sheets: 0 ka BP The remaining simulations explore the climate response to a change in one of these forcings, with all other forcings set to preindustrial levels. Forcings are specified as follows: - lo_obliq and hi_obliq: Obliquity is set to 22.079° or 24.480°, respectively. - 0_AEQ, 90_WSOL, 180_VEQ, and 270_SSOL: Perihelion occurs at the NH autumnal equinox, winter solstice, vernal equinox, or summer solstice, respectively, with eccentricity set to 0.0493. This corresponds to a longitude of perihelion of 0°, 90°, 180°, or 270°, respectively. - ECC_0: Eccentricity is set to 0. - half_CO2: CO 2 is set to 143 ppm. - ice_sheets: Ice sheets and sea level are set to Last Glacial Maximum (LGM) levels. Ice sheets come from the ICE-5G reconstruction. A note about preindustrial ...